The Impact of Essential Oils Derived from Citrus Species to Control Botrytis cinerea and Their Potential Physiological Actions - Sebastián Campos; Javier Espinoza; Juan Mauricio Fuentes; Ignacio Jofré-Fernández; Gonzalo Tortella; Diego Navarro; Andrés Quiroz; María Cristina Diez; Olga Rubilar; Paola Fincheira (Plants)
Botrytis cinerea is one of the phytopathogenic fungi of the greatest economic importance worldwide. Essential oils (EOs) have been proposed as a sustainable alternative to reduce the growth of phytopathogenic fungi. Nevertheless, few studies exist about its mechanisms of action. This study evaluated the antifungal activity of EOs from Citrus reticulata, Citrus limon, Citrus sinensis, and Citrus paradisi peels and their encapsulation inside solid lipid nanoparticles (SLNs). Accordingly, Citrus EOs were mainly constituted by monoterpene hydrocarbons, where limonene was the most abundant in all EOs. C. reticulata and C. limon EOs reduced the mycelial growth at above 54% after 96 h. The other EOs did not significantly impact the phytopathogen. C. reticulata EO increased the hyphae damage by 40%, but the spore germination was reduced by only 8.34%. It also significantly increased the pH, the electrical conductivity, and the release of intracellular absorbing material and soluble proteins in B. cinerea cultures. Contrary, the esterase, mitochondrial, and succinate dehydrogenase activities decreased at above 50%. C. reticulata EO into SLN reduced the mycelial growth of B. cinerea by 90–97%. These results show that the EO of C. reticulata alters the physiological and metabolic activities of B. cinerea to reduce its growth.